The role of air-water interface in the SO3 hydration reaction. (1st June 2020) - Lv, Guochun; Sun, Xiaomin
Abstract: H2 SO4 is an important pollutant in the atmosphere, and it mainly be formed through the oxidation of SO2 . SO3 produced from the oxidation of SO2 is a precursor of H2 SO4 . Considering that understanding of SO3 hydration reaction at the air-water interface is limited, we combined the classical molecular dynamics simulations (classical MD) with Born–Oppenheimer MD simulations and ab initio calculations to study the SO3 reaction with H2 O at air-water interface. The free energy and impinging results indicate that the SO3 molecules can easily be trapped by water droplets. After uptake by the interface, the SO3 can react rapidly with water molecules to form the ion pair of HSO4 − and H3 O + or H2 SO4 within a few picoseconds. In the interfacial hydration mechanism, the loop-structure formation is not prerequisite of the hydration reaction, which is obviously different from the corresponding gas-phase hydration reaction of SO3 . The work is meaningful for understanding the heterogeneous formation of H2 SO4 and the contribution of interfacial reaction to the new particle formation. Highlights: SO3 can easily be trapped by water droplets. The SO3 hydration mechanism at the air-water interface was considered. The loop-structure formation is not prerequisite of interfacial hydration of SO3 .